Carbon farming in Africa: Opportunities and challenges for engaging smallholder farmers - Friederike Schilling; Heike Baumüller; Julius Ecuru; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2023)
The Intergovernmental Panel on Climate Change (IPCC) highlights the importance of reaching net-zero CO2 emissions globally by 2050. Unlocking the potential of natural climate solutions in the strive for net-zero emissions is increasingly gaining attention. A large potential may arise from the adoption of agricultural practices that increase carbon sequestration in soils and plants and reduce or avoid greenhouse gas (GHG) emissions in agricultural production, referred to as carbon farming. In practice, existing markets fail to internalize environmental externalities, creating a mismatch between individual costs and societal benefits of carbon farming. One solution to bridge this gap are payments linked to the implementation of carbon farming practices. To support the development of wellfunctioning agricultural carbon markets, supporting research is crucial. We assessed the opportunities and challenges for involving smallholder farmers in emerging agricultural carbon markets. We placed a specific emphasis on summarizing the state of knowledge in four areas: i) agricultural markets as a funding institution for carbon farming, ii) the role of payments for carbon sequestration in incentivizing the adoption of carbon farming practices, iii) the scaling of smallholder farmers' opportunities in carbon farming by capitalizing on farming groups, and iv) the cost-effective monitoring, reporting and verification of changes in carbon stocks. Further research that supportsthe accurate and cost-effective monitoring of carbon sequestration, reduction and avoidance of GHG emissions as well as implementation research that focuses on the institutional arrangements required to tap potentials for carbon credits to promote sustainable production methods in Africa will be needed.
Keywords: H23; O13; Q10; Q20; Q56; Q57; 330; carbon farming; carbon sequestration; carbon markets; payment for ecosystem services; sustainable agriculture